NUMERICAL ANALYSIS OF WATER RESOURCE DYNAMICS IN THE SOUTH ARAL SEA REGION FOR 2000–2025 - Djengisbaevna, Payzullaeva Ayzada; Adilbaevna, Kipshakbaeva Gauxar; Tleubergenovna, Berdimbetova Amina; Tleubergenovich, Berdimbetov Timur (Research Focus International Scientific Journal, 2026)
This article focuses on the numerical analysis of water resource dynamics in the Aral Sea region, mainly in its southern part, for the period 2000–2025, based on the methodology of working with global models and remote sensing data.